Impact of COVID-19 on English Football Premier League: analyzing rankings and home advantage using extended Bradley-Terry models - Liu, H. H.; Battaglia, J.; Wu, T. T. (PLOS ONE, 2025)
COVID-19 significantly impacted sports tournaments, particularly soccer. During the pandemic, restrictions on spectators and frequent team composition changes due to outbreaks, providing a unique opportunity to explore the effects on team performance and home advantage (HA). In this study, we have two focuses. We first introduce a new extended Bradley-Terry model. The proposed model demonstrated several advantages over existing models, particularly in terms of stability, ease of implementation, and interpretation. It can be applied to any sport featuring home and away dynamics. The second focus is to apply the proposed model to data from the English Premier League over the past ten seasons. The analysis aims to evaluate changes in team rankings and home advantage before, during, and after the pandemic disruptions. Our findings indicate marked fluctuations in team performance and home advantage during the pandemic, with a distinct shift in team dynamics and competitive balance under pandemic restrictions.